Comparison of sequential and simultaneous chemo-radiotherapy for advanced hypopharyngeal carcinoma - Results of a randomized study - Iro, H... (Radiology and oncology (Ljubljana), 1997)
In prospective randomized study, a comparison was drawn between intensified sequential chemo-therapy (arm A) and simulatenous chemo-radiotherapy (arm B) in stage IV hypopharyngeal cancer. G-CSF support was given in both arms; chemotherapy consisted of 2 courses of CDDP (25 mg/m2/d for 5 days) and 5-FU (750 mg/m2/d for 5 days continously). Radiotherapy dosages were 70 Gy on the primary lesion and 60 Gy on the neck. Ninety eight patients were randomized; 60 patients (28 arm A, 32 arm B) finally fulfilled inclusion criteria. Complete remission could be observed in 49% in arm A and in 57% in arm B (p=0.07) and the two-year survival was 27% and 47%, respectively.
Keywords: Drug therapy; Hypopharyngeal neoplasms; Radiotherapy; Treatment outcome